2016
DOI: 10.3945/ajcn.115.120881
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal nutrition on breast-milk composition: a systematic review,

Abstract: The available information on this topic is scarce and diversified. Most of the evidence currently used in clinical practice to make recommendations is limited to studies that only reported indirect associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
311
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(335 citation statements)
references
References 51 publications
(235 reference statements)
13
311
2
9
Order By: Relevance
“…Other stakeholders have been specifically addressed with targeted communication. Evidence-based recommendations on optimized practice of nutrition before and during pregnancy, during the breast feeding period and the early life of infants, have been developed based on the project results and on systematic reviews of available evidence [35,36,37,38,39,40,41,42], in close collaboration with a broad group of stakeholders (prepared for publication). These recommendations are of considerable importance because most of the current guidance for pregnant women, particularly obese women, and for young children does not take into account the long-term programming consequences of early nutrition.…”
Section: Further Disseminationmentioning
confidence: 99%
“…Other stakeholders have been specifically addressed with targeted communication. Evidence-based recommendations on optimized practice of nutrition before and during pregnancy, during the breast feeding period and the early life of infants, have been developed based on the project results and on systematic reviews of available evidence [35,36,37,38,39,40,41,42], in close collaboration with a broad group of stakeholders (prepared for publication). These recommendations are of considerable importance because most of the current guidance for pregnant women, particularly obese women, and for young children does not take into account the long-term programming consequences of early nutrition.…”
Section: Further Disseminationmentioning
confidence: 99%
“…For instance, no changes have been observed in proteins, and mineral composition (Innis, 2014). However, diet can affect the content of fatty acids and vitamins, such as vitamin B1 and C composition (Bravi et al, 2016). As a consequence it has been suggested that diet can affect the concentrations of gangliosides, such as GM3 and GD3 in human milk (Giuffrida, Elmelegy, Thakkar, Marmet, & Destaillats, 2014).…”
Section: Maternal Factorsmentioning
confidence: 99%
“…6 The fat fraction appears to be the most sensible to maternal diet whereas the protein and carbohydrate fraction appear not to be affected. 7 The specific fatty acids in human milk, either synthetized endogenously in the mammary gland or taken up from maternal plasma, reflect changes in the maternal dietary fat within two-three days. Maternal body mass index also contributes to modulate the amount and type of human milk fatty acids; specifically, the amount of saturated fatty acids and the ratio of n-6 to n-3 fatty acids are higher in overweight women's breast milk than in normal weight women's breast milk, also after taking into account maternal diet.…”
Section: Introductionmentioning
confidence: 99%